Algorithmic brand culture: participatory labour, machine learning and branding on social media. (March 2018) - Carah, Nicholas; Angus, Daniel
Social media platforms like Facebook and Instagram have transformed how brands operate as cultural processes. Over the past decade, these platforms have engineered an algorithmic brand culture that combines the participatory affordances and data-processing power of digital media. In the brand culture of social media, the creative narration of cultural experience doubles as data that trains platform algorithms. We develop an account of the algorithmic brand culture of social media via a case study of the Splendour in the Grass music festival, the activations sponsoring brands build at the festival, and the participatory mediation of the festival on Instagram. Brands play a critical role in both funding and engineering social media platforms, and integrating them into cultural experience. We argue for the development of critical cultural and computational approaches that examine how the use of machines to make judgments about cultural life is intrinsic to capitalising on the participatory nature of brand culture. Media researchers must go beyond describing the content of user-generated content on platforms to critically simulate and scrutinise media platforms' algorithmic infrastructure.